Effect of a constant rate infusion of cytosine arabinoside on mortality in dogs with meningoencephalitis of unknown origin. (July 2016) - Lowrie, M.; Thomson, S.; Smith, P.; Garosi, L.
Highlights: Cytosine arabinoside was administered to dogs with meningoencephalitis of unknown origin (MUO). Dogs were treated with cytosine arabinoside subcutaneously (SC) or by constant rate infusion (CRI) along with prednisolone. Survival, cerebrospinal fluid (CSF) abnormalities and magnetic resonance imaging (MRI) lesions at 3 months were compared. Constant rate infusion produced a survival advantage over subcutaneous administration without evidence of toxicity. MRI and CSF abnormalities at 3 months were improved in dogs receiving CRI compared to SC administration. Abstract: Administration of cytosine arabinoside (CA) by continuous rate infusion (CRI) has pharmacokinetic and pharmacodynamic advantages over traditional intermittent dosing. Whether these advantages translate into clinical efficacy remains unknown. The aim of this study was to assess the efficacy and safety of CRI of CA in dogs with meningoencephalitis of unknown origin (MUO) and to compare outcomes with a group of historical control dogs treated with conventional intermittent subcutaneous (SC) administration of CA; both groups received adjunctive prednisolone. It was hypothesised that a CRI of CA for 24 h at 100 mg/m 2 would improve survival and lesion resolution compared with conventional SC delivery of 50 mg/m 2 every 12 h for 48 h. Eighty dogs with suspected MUO were recruited from consecutive dogs presenting with suspected MUO from 2006 to 2015. All dogs underwent routine clinical evaluation, magnetic resonance imaging of the brain and cerebrospinal fluid analysis. There were 39 dogs in the SC group and 41 dogs in the CRI group; baseline characteristics were similar in both groups. Survival at 3 months was 22/39 (44%) with SC delivery versus 37/41 (90%) with CRI. No dose-limiting toxicities were noted for either group. The resolution rate of magnetic resonance imaging and cerebrospinal fluid abnormalities at the 3 month re-examination were substantially improved in the CRI group versus the SC group. The CRI regimen produced a survival advantage over the SC route of administration without clinically significant toxicity. These data supports the routine use of CRI at first presentation for the treatment of MUO in dogs.